Pluralist Universalism : An Asian Americanist Critique of U.S. and Chinese Multiculturalisms - Jin, Wen, 1977- (Book collections on Project MUSE., 2012)
"The "double critique" framework builds upon critical perspectives developed in Asian American studies and adjacent fields. The book brings to life an innovative vision of Asian American literary critique, even as it offers a unique intervention in ideas of ethnicity and race prevailing in both China and the United States in the post-Cold War era"--Publisher's description.